2009
DOI: 10.4149/neo_2009_03_275
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of KRAS mutation status in metastatic colorectal cancer patients

Abstract: colorectal carcinoma (crc) represents a serious problem worldwide: in the slovak republic are diagnosed about 2600 new crc cases annually and its incidence is increasing. colorectal cancer patients may succumb to the disease because of local recurrence or local formation of metastasis. Therefore, it is necessary to modulate therapeutic algorithm with new methods, leading to early diagnostic of crc or changing the existing therapeutic procedures. recent progresses have been made in understanding of eGFr pathway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 14 publications
(16 reference statements)
0
6
0
Order By: Relevance
“…Little data are available on the use of pyrosequencing in clinical practice, whereas some studies have compared PCR/sequencing and DxS [12][13][14][15][16][17]27]. These two methods showed comparable sensitivity in two studies in which small cohorts of patients were analyzed [13,14].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Little data are available on the use of pyrosequencing in clinical practice, whereas some studies have compared PCR/sequencing and DxS [12][13][14][15][16][17]27]. These two methods showed comparable sensitivity in two studies in which small cohorts of patients were analyzed [13,14].…”
Section: Discussionmentioning
confidence: 98%
“…Few studies have compared the results of the DxS and PCR/sequencing methods in the same cohort of patients with contrasting results [12][13][14][15][16][17].…”
mentioning
confidence: 99%
“…[61][62][63] Separate studies have also reported that the rate of K-ras mutation is enhanced in CRC patients with lung metastasis 64 and that the presence of K-ras mutations in CRC patients with liver metastasis is predictive of bad prognosis. 65 Analysis of the mutational state of ras genes has proven to be very significant for selection of therapeutic approaches in CRC.…”
Section: Pancreatic Ductal Adenocarcinomamentioning
confidence: 96%
“…Several studies demonstrated constitutive activating KRAS, BRAF, and PIK3CA mutations in CRC, with KRAS mutations being most frequent at 27-45 % [ 35 , 47 -50 ]. Interestingly, activating KRAS mutations appear early in the genesis of CRC, with mutations found in adenomatous polyps [ 50 ]. Most activating KRAS mutations exhibit GTPase activity loss combined with GTPase-activating protein insensitivity [ 32 ].…”
Section: Egfr Kras and De Novo Crcmentioning
confidence: 99%